Mesenchymal Stem Cell-Derived Exosomes Promote Fracture Healing in a Mouse Model - Furuta, Taisuke (Stem Cells Transl Med, 2016)
Paracrine signaling by bone-marrow-derived mesenchymal stem cells (MSCs) plays a major role in tissue repair. Although the production of regulatory cytokines by MSC transplantation is a critical modulator of tissue regeneration, we focused on exosomes, which are extracellular vesicles that contain proteins and nucleic acids, as a novel additional modulator of cell-to-cell communication and tissue regeneration. To address this, we used radiologic imaging, histological examination, and immunohistochemical analysis to evaluate the role of exosomes isolated from MSC-conditioned medium (CM) in the healing process in a femur fracture model of CD9(−/−) mice, a strain that is known to produce reduced levels of exosomes. We found that the bone union rate in CD9(−/−) mice was significantly lower than wild-type mice because of the retardation of callus formation. The retardation of fracture healing in CD9(−/−) mice was rescued by the injection of exosomes, but this was not the case after the injection of exosomes-free conditioned medium (CM-Exo). The levels of the bone repair-related cytokines, monocyte chemotactic protein-1 (MCP-1), MCP-3, and stromal cell-derived factor-1 in exosomes were low compared with levels in CM and CM-Exo, suggesting that bone repair may be in part mediated by other exosome components, such as microRNAs. These results suggest that exosomes in CM facilitate the acceleration of fracture healing, and we conclude that exosomes are a novel factor of MSC paracrine signaling with an important role in the tissue repair process. SIGNIFICANCE: This work focuses on exosomes, which are extracellular vesicles, as a novel additional modulator of cell-to-cell communication. This study evaluated the role of exosomes isolated from mesenchymal stem cell (MSC)-conditioned medium (MSC-CM) in the fracture-healing process of CD9(−/−) mice, a strain that is known to produce reduced levels of exosomes. Retardation of fracture healing in CD9(−/−) mice was rescued by the injection of MSC exosomes, but this was not the case after the injection of exosome-free CM. This study finds that MSC exosomes are a novel factor of MSC paracrine signaling, with an important role in the tissue repair process.